Cobalt Modulates Healing of Gastric Ulceration in Male Wistar Rats: iNOS/COX-2 Crosstalk (Nigerian Journal of Pharmaceutical Research, 2025)
Background: Information on the interplay between gastric iNOS and COX-2 expression by Cobalt (CoCl2) during gastro-protection is unclear.Objective: Cobalt activities on iNOS and COX-2 interplay was investigated using Reserpine (RGU), and Pyloric-ligation (PLGU) gastric ulcer models.Materials and Methods: In RGU, 50 Wistar rats grouped; 1-control, 2-ulcerated untreated (RUU), 3, 4, and 5 were ulcerated pre-treated with 62mg/kg, 25mg/kg CoCl2 and 3.6mg/kg omeprazole for 5 days and sacrificed 3 and 8 hours after reserpine administration. In PLGU, 25 Wistar rats grouped; A-25mg/kg Cocl2, B-62mg/kg Cocl2, C-Cimetidine (36.88mg/kg), D-ulcerated untreated (UU), and E–control, were pretreated for 8 days prior 18 hours pyloric-ligation. Thereafter, macroscopic gastric ulceration (GU), biochemical analysis with histology, and immunohistochemistry were evaluated on excised stomach. Data were expressed as Mean+SEM, and p